Aggregation‐Induced Quenching of Carbon Dots for Detection of Nitric oxide. Issue 21 (1st June 2022) - Mutreja, Vishal; Kumar, Ajay; Sareen, Shweta; Pathania, Khushboo; Sandhu, Harshit; Kataria, Ramesh; Pawar, Sandip V.; Mehta, Surinder K.; Park, Jeongwon
Abstract: This study reports the synthesis of three types of carbon dots (CDs) prepared using citric acid as a carbon source and three different biomolecules (L‐serine, L‐threonine, and adenine) individually as an amine source. The obtained nanomaterials were characterized by powder XRD, TEM, FTIR, 13 C NMR, distortionless enhancement by polarization transfer using a 135‐degree decoupler pulse (DEPT 135), dynamic light scattering (DLS), and Small‐Angle X‐ray Scattering (SAXS) techniques. After ensuring the formation of desired structures, prepared CDs were used for exploring the detection capabilities of different reactive nitrogen species and reactive oxygen species. Following the screening of their detection capabilities specifically for nitric oxide, different sensing parameters viz the limit of detection, quenching constant, and interferences were evaluated. Among the synthesized CDs, the lowest detection limit of 0.1 μM was determined for the serine‐derived dots while 0.12 and 0.19 μM was obtained for adenine and threonine‐derived dots, respectively. Eventually, a possible sensing mechanism for the detection of NO by the prepared nanomaterials is proposed. Abstract : Amine decorated carbon dots prepared using citric acid and biomolecules.